Thrifting for More: Savings and Aspirations in Health Care Sharing Ministries after the Affordable Care Act. (29th April 2019) - Schwarz, Carolyn
Abstract: The Affordable Care Act (ACA) of 2010 includes health care sharing ministries (HCSMs) on the list of religious exemptions to the individual mandate. HCSMs are non‐profit, faith‐based organizations that share in the cost of medical bills but are not actually insurance. Precisely because HCSMs are not beholden to any of the ACA's insurance reforms, they have the advantage of costing less. Based primarily on in‐depth interviews, I argue that thrift is the preeminent moral discourse that anchors the HCSM world. For members, thrift in health care is understood as a moral good and as a practice that offers possibilities for benefiting connected others and generating life fulfillment, or what Taylor refers to as "fullness." I suggest that a focus on thrift raises questions about how Americans make determinations about worth in health care and how they construct health care–seeking as deeply attached to their visions of how they want life to be.